On the solutions of fractional Swift Hohenberg equation with dispersion - Vishal K.; Das S.; Ong S.H.; Ghosh P. (My University, 2025)
In this article, the approximate solutions of the non-linear Swift Hohenberg equation with fractional time derivative in the presence of dispersive term have been obtained. The fractional derivative is described in Caputo sense. Time fractional nonlinear partial differential equations in the presence of dispersion and bifurcation parameters have been computed numerically to predict hydrodynamic fluctuations at convective instability for different particular cases and results are depicted through graphs. © 2012 Elsevier Inc. All rights reserved.